Coding accuracy is not fully determined by the neuronal model - Kostal, Lubomir; Lansky, Petr (Neural computation, 2015)
It is automatically assumed that the accuracy with which a stimulus can be decoded is entirely determined by the properties of the neuronal system. We challenge this perspective by showing that the identification of pure tone intensities in an auditory nerve fiber depends on both the stochastic response model and the arbitrarily chosen stimulus units. We expose an apparently paradoxical situation in which it is impossible to decide whether loud or quiet tones are encoded more precisely. Our conclusion reaches beyond the topic of auditory neuroscience, however, as we show that the choice of stimulus scale is an integral part of the neural coding problem and not just a matter of convenience.
Keywords: Models, Neurological; Humans; Algorithms; modely neurologické; Loudness Perception; nervové vedení; Computer Simulation; Acoustic Stimulation; nervus cochlearis; lidé; stochastické procesy; vnímání hlasitosti; nervová vlákna; Neural Conduction; počítačová simulace; Cochlear Nerve; algoritmy; Nerve Fibers; Stochastic Processes; akustická stimulace